Photochromism of the Synthetic 4',7-Dihydroxyflavylium Chloride - Figueiredo, Paulo (2018)
The synthetic compound 4',7-dihydroxyflavylium chloride shows an interesting photochromic effect at moderately acidic pH values. Pale yellow solutions of this compound, equilibrated in the dark at pH 3.4, become bright yellow upon irradiation with 313-nm light. Switching off the light, gives back the initial pale yellow solution. Photochemical methods, *H NMR, and molecular orbital calculations were used to elucidate this photochromic behavior. In solutions equilibrated in the dark (pH < 5.7), the existence of two main species in equilibrium is demonstrated: the colored flavylium cation and the colorless ira/w-chalcone. Freshly prepared solutions of this compound at pH 6.2 reveal the existence of another colored form, the quinonoidal base, which reacts thermally to yield froni-chalcone. An analogous reaction takes place in freshly prepared solutions at pH 3.4: the flavylium cation is partially converted into tre/w-chalcone. The extent of such conversion is pH dependent and nearly complete at pH 6.2. Irradiation of trans- chalcone at the wavelength of 313 nm partially gives back the initial colored form, with concomitant formation of small amounts of photodegradation products. The turnover of the photochromic reaction is greater at pH 3.4 than at pH 6.2. The photochromism is explained on the basis of a trans-cis photoisomerization. In fact the relative stability of the two chalcone isomers is reversed in the excited state, as predicted from molecular orbital calculations